The Pelatihan pemanfaatan media online sebagai sarana pemasaran bagi usaha mikro dimasa pandemi di kota depok - Hafniza Amir; Eva Zulfa Nailufar; Mawarta Onida Sinaga (BEMAS: Jurnal Bermasyarakat, 2023)
The Business Administration study program takes part in volunteer activities with a community-based science and technology service scheme. This service is performed to improve microbusinesses' understanding of digital marketing in the city of Depok with the aim of expanding the marketing area, which will have an impact on income. This activity employs a contextual approach methodology, whereby theoretical information is initially provided, and then a workshop immediately creates an account on online media and uploads products made by traders. In order to allow participants who are unable to attend at the service venue to participate in this community service activity elsewhere by using the Zoom platform. The participants were given counseling from the very beginning of the process of downloading an account creation program, building a digital store, and marketing product photographs with narration and descriptions of the product, the participants received coaching. The participants were very excited to participate in the series of events that had been planned by the committee, both in listening to the speaker's presentation and when carrying out implementation practices in online media. sale. This activity ran smoothly and in good order from the morning until the afternoon